Feeding management before gastrointestinal studies in pigs. (April 2021) - Gregson, Rachael; Greenhalgh, Stephen; Cox, Benjamin; Cochrane, Sandy; Clutton, R Eddie
Pigs are used to model humans in gastrointestinal (GI) studies because of their comparable size, physiology and behaviour: both are monogastric omnivores. A porcine surgical model for testing novel, tethered ultrasound capsule endoscopes (USCE) requires a clean, motile small intestine. Recommendations for human GI tract preparation before the mechanically similar process of video capsule endoscopy describe using oral purgatives, while high-carbohydrate drinks are recommended before colorectal surgery. Reports of the GI preparation of pigs exist but lack technical details, that is, administration, efficacy and side effects. This report details feeding a high-energy liquid diet to 11 female pigs undergoing surgery and USCE which was readily accepted and easily administered, and which produced a clean, motile small intestine and caused no detectable physiological/behavioural abnormalities.